Kredibilitas Informasi dalam Perspektif Modern dan Islam: Telaah terhadap Penggunaan Hadis Dha’if - Hilyatul Khoiri, Nikmah (Institut Muslim Cendekia, 2025)
This article examines the relevance between the concept of information credibility in modern discourse and the hadith criticism in Islamic tradition, particularly regarding the use of weak (dha’if) hadith. Employing a library research method, the study draws parallels between digital media literacy criteria and classical methodologies for hadith validation. The findings reveal that both modern and traditional frameworks emphasize scrutiny of the source, content, and objectivity. The study also discusses scholarly debates on the acceptability of dha’if hadith and reflects on the need for cautious engagement with online information. The paper concludes by emphasizing the importance of educational awareness in navigating religious and general knowledge dissemination in contemporary media.